2017
DOI: 10.1016/j.cell.2017.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Reprogramming in the Liver Identifies Metabolic Pathways of Aging

Abstract: The process of aging and circadian rhythms are intimately intertwined, but how peripheral clocks involved in metabolic homeostasis contribute to aging remains unknown. Importantly, caloric restriction (CR) extends lifespan in several organisms and rewires circadian metabolism. Using young versus old mice, fed ad libitum or under CR, we reveal reprogramming of the circadian transcriptome in the liver. These age-dependent changes occur in a highly tissue-specific manner, as demonstrated by comparing circadian ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
283
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(320 citation statements)
references
References 75 publications
29
283
0
Order By: Relevance
“…Calorie restriction (CR) delays aging and increases longevity in a variety of organisms (11,12) and affects circadian clocks. CR changes circadian rhythms in behavior and gene expression, thus regulating both central and peripheral circadian clocks, and the effect is conserved between flies and rodents (13)(14)(15)(16)(17). Circadian clocks are master regulators of metabolism (18), and it was speculated that at least some of the beneficial outcomes of CR are due to the effect on the clock (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Calorie restriction (CR) delays aging and increases longevity in a variety of organisms (11,12) and affects circadian clocks. CR changes circadian rhythms in behavior and gene expression, thus regulating both central and peripheral circadian clocks, and the effect is conserved between flies and rodents (13)(14)(15)(16)(17). Circadian clocks are master regulators of metabolism (18), and it was speculated that at least some of the beneficial outcomes of CR are due to the effect on the clock (2,3).…”
mentioning
confidence: 99%
“…Circadian clocks are master regulators of metabolism (18), and it was speculated that at least some of the beneficial outcomes of CR are due to the effect on the clock (2,3). Recent analysis of circadian rhythms of mRNA abundance in the liver and skeletal muscles of young and old mice fed ad libitum (AL) or CR diets identifies a significant reprogramming of the circadian transcriptome by aging and CR (16,19), supporting the importance of the interaction between biologic clocks, diet, and aging.…”
mentioning
confidence: 99%
“…Other examples further demonstrate that liver circadian rhythms can be affected by extrinsic factors. When comparing young versus old mice, Sato et al () observed age induced reprogramming of the circadian hepatic transcript and chromatin landscapes. However, caloric restriction, which has been associated with clock re‐setting (Guan et al, ), counteracted age‐dependent changes (S. Sato et al, ).…”
Section: Liver Enhancer Dynamicsmentioning
confidence: 99%
“…When comparing young versus old mice, Sato et al () observed age induced reprogramming of the circadian hepatic transcript and chromatin landscapes. However, caloric restriction, which has been associated with clock re‐setting (Guan et al, ), counteracted age‐dependent changes (S. Sato et al, ). Earlier work has also established the role of body temperature as a universal cue in mammalian circadian transcriptional regulation (Buhr, Yoo, & Takahashi, ).…”
Section: Liver Enhancer Dynamicsmentioning
confidence: 99%
“…Yet, SIRT1 may be beneficial under specific circumstances to regulate circadian rhythm gene expression that can foster hepatocellular proliferation and liver regeneration following liver resection (156). More recent work also suggests an important role for SIRT1 targets with aging and circadian gene expression in the liver (157). …”
Section: Circadian Clock Genesmentioning
confidence: 99%